(untitled) (Journal of Sustainability, Environment and Peace, 2020)
Disposal of leather waste from urban tanneries is a major challenge. Sustainable and environmentally friendly methods are required in urban settings. This paper therefore, deals with the identification and quantification of all types of tanned solid wastes generated by 6 pre-selected urban tanneries in Kenya vis a vis corresponding quantity of hides and skins processed. Questionnaire survey and key informant interviews were conducted. The data collected in this study was analysed using descriptive statistics, and the analysis showed that 1,443,000kg of chromium contaminated leather waste was generated by the 6 pre-selected tanneries in the month of study. The generated wastes constituted chrome shavings (32.1%), chrome splits and trimmings (36.2%), vegetable shavings (9.1%), vegetable splits and trimmings (14.9%), crust trimmings (3.5%), buffing dust (2.4%) and finished trimmings (1.8%), all of which amounted to 2,112,560kg for one month in the 6 pre-selected tanneries that were investigated. The current modes of disposal of the waste include landfilling, dumping in open grounds, and or incineration. Out of the total amount of hides processed in the 6 pre-selected tanneries during the month of study (6,642,525kg), 31.8% of this amount (i.e. 2,112,560kg) was actually converted into leather solid wastes. The proportion of leather solid wastes generated vis a vis the corresponding amount of hides processed was found to match closely with what is reported in literature (standard practice). It was also established in this study that chromium-containing leather waste formed the highest percentage (68.3%) of the various types of leather solid wastes generated in the 6 tanneries that were investigated.